Penerapan Model Active Learning Tipe Quiz Team Untuk Meningkatkan Motivasi Belajar Siswa - Andani, Pindri Dewi; Sunanto, Liyana (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2023)
This research is motivated by a lack of interest in learning in students and requires the use of more creative learning models so as to make learning more interesting, there are students who do not do assignments, this occurs because of a lack of motivation to learn in students. The purpose of this study was to increase student motivation by using the Quiz Team Type Active Learning model, where the implementation of this research was carried out at SDIT As Salam Kampung Simpur, Ciantra Village, South Cikarang District, Bekasi Regency, for the 2022/2023 Academic Year. This study uses a class action research method, with the Kemmis-Mc design model. Tagart, the subjects of this study were 20 fourth grade students. Based on the results of this study, the application of the Quiz Team Type Active Learning model for students in cycle I was in the good category and cycle II was in the very good category. Thus the Quiz Team Type Active Learning model is effective in increasing student motivation.